PARAMETERS OF ACUTE TOXICITY AND TOXIC EFFECTS OF THE SYNTHETIC PYRETHROID ASHIMETHRIN ALPHA ON THE ANIMAL BODY (INTERNATIONAL JOURNAL OF SCIENCE AND TECHNOLOGY, 2025)
The article presents the results of studying the acute toxicity of the synthetic pyrethroid ashimethrin alpha (Achich Life Science Put.Ltd., India) on the body of rabbits and Karakul sheep. To determine the main toxicometric parameters, experimental rabbits were given ashimethrin alpha orally once in the form of a 10% suspension at doses of 1300, 1375, 1450, 1525 and 1600 mg / kg, and Karakul sheep received doses of 200, 275, and 350 mg/kg (based on the active ingredient). Studies have established that LD50 for rabbits is 1450.00 mg/kg, and for sheep 347.79 mg/kg. Our observations showed that oral administration of the studied pyrethroid to rabbits at doses of 1375-1600 mg / kg and Karakul sheep 275-350 mg / kg 3 hours after administration caused poisoning with neurotoxicity, death usually occurred within the first 48 hours. During the experiment, violations of the morphological, biochemical and immunological parameters of animal blood were observed. Ashimethrin alpha was quickly absorbed in the gastrointestinal tract, followed by distribution and accumulation in the spleen, liver, and myocardium. The maximum levels of pyrethroid were found in the contents of the stomach (rumen) of dead and involuntarily killed rabbits and Karakul sheep. Complete elimination of the drug was completed after 28 days, according to the results of the veterinary and sanitary examination, the slaughter products fully met the requirements of GOST.